How do general practitioners implement decision-making regarding COPD patients with exacerbations? An international focus group study - Laue,Johanna; Melbye,Hasse; Halvorsen,Peder; Andreeva,Elena; Godycki-Cwirko,Maciek; Wollny,Anja; Francis,Nick; Spigt,Mark; Kung,Kenny; Risør,Mette (International Journal of Chronic Obstructive Pulmonary Disease, 2016)
Johanna Laue,1 Hasse Melbye,1 Peder A Halvorsen,1 Elena A Andreeva,2 Maciek Godycki-Cwirko,3 Anja Wollny,4 Nick A Francis,5 Mark Spigt,6 Kenny Kung,7 Mette Bech Risør1 1Department of Community Medicine, General Practice Research Unit, University of Tromsø – The Arctic University of Norway, Tromsø, Norway; 2Department of Family Medicine, Northern State Medical University, Arkhangelsk, Russia; 3Department of Family and Community Medicine, Medical University of Lodz, Lodz, Poland; 4Institute of General Practice, University Medical Center Rostock, Rostock, Germany; 5Cochrane Institute of Primary Care and Public Health, School of Medicine, Cardiff University, Cardiff, UK; 6CAPHRI School for Public Health and Primary Care, Maastricht University, Maastricht, the Netherlands; 7The Jockey Club School of Public Health and Primary Care, The Chinese University of Hong Kong, Hong Kong Purpose: To explore the decision-making of general practitioners (GPs) concerning treatment with antibiotics and/or oral corticosteroids and hospitalization for COPD patients with exacerbations.Methods: Thematic analysis of seven focus groups with 53 GPs from urban and rural areas in Norway, Germany, Wales, Poland, Russia, the Netherlands, and Hong Kong.Results: Four main themes were identified. 1) Dealing with medical uncertainty: the GPs aimed to make clear medical decisions and avoid unnecessary prescriptions and hospitalizations, yet this was challenged by uncertainty regarding the severity of the exacerbations and concerns about overlooking comorbidities. 2) Knowing the patient: contextual knowledge about the individual patient provided a supplementary framework to biomedical knowledge, allowing for more differentiated decision-making. 3) Balancing the patients’ perspective: the GPs considered patients’ experiential knowledge about their own body and illness as valuable in assisting their decision-making, yet felt that dealing with disagreements between their own and their patients’ perceptions concerning the need for treatment or ...